Preliminary Study on Larvae Production of Yellow Pufferfish, Xenopterus naritus - Nurin Syahindah Syasya, Nor Ashikin (Universiti Malaysia Sarawak(UNIMAS), 2015)
This study was carried out to document the embryonic development, larvae rearing and production of Tetrodotoxin (TTX) in yellow pufferfish, Xenopterus naritus larvae from Batang Saribas, Sarawak. The broodstock was captured by using single layer gill nets with mesh size of 6.4 cm. An artificial fertilization was conducted on-site to obtain the larvae. Different stages of embryonic and larvae development were described from fish kept at 22°C in the laboratory. At 24-DAH, the meristic measurements of larvae are 32, 22 and 22 for dorsal, anal and caudal fin rays. The larvae were reared at different treatment of photoperiod, salinity and feeding. Good survival was achieved by adopting the photoperiod 9L 15D, salinity 15 ppt and diets on artemia with 28%, 36% and 8% of survival rate percentage respectively. The highest growth rate was seen in 24L photoperiod treatment followed by 24D with 0.10 and 0.05 and the lowest growth observed in 9L 15D (0.0125 mm days-1) treatment. The properties, level and amount of TTX in larvae and tissues of adult X. naritus were tested by using Thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC) and Liquid Chromatography–Mass Spectrometry (LC-MS) Toxin Analysis respectively. The Rf value of TLC in buffer 1 and buffer 2 shows that egg tissue has the nearest Rf value with the standard value which is 0.98 and 0.25. The amount of TTX contains in larvae by using HPLC and LC-MS is 4283.18 and 504.13 MU/g. While the egg scores the highest amount of TTX when analyses by HPLC (459.55 MU/g) and 1942.28 MU/g when analysed with LC-MS. The other tissues were considered non- toxic.